Hedging against inflation: housing versus equity - Daniel Fehrle (Empirical Economics, 2023)
To which extent do equity and housing hedge against inflation? Despite the extensive literature, there is only little consensus. This paper presents evidence on this question from the Jordà–Schularick–Taylor Macrohistory Database covering 16 countries from 1870 to 2020. The results depend on the time horizon and period considered. Within a 1-, 5-, and 10-year horizon, housing at least partially hedges against inflation. The nominal return–inflation relation is higher in the post-war period. In the long run, housing hedges excessively in the whole sample and perfectly in the post-war period. Equity provides no hedge within 1 year in the entire period, and the returns tend to decrease with inflation in the post-war period. The hedge improves slightly with a longer time horizon and is perfect in the long run in the post-war period. Thus, housing is at least weakly superior in hedging against inflation. The results are robust to a non-housing consumption price index and an asset price appreciation approach.
Keywords: C22; C23; E31; E44; G11; N10; 330; Hedge; Inflation; Stocks; Real estate; Classical dichotomy